2018
DOI: 10.1136/sextrans-2017-053478
|View full text |Cite
|
Sign up to set email alerts
|

National prevalence estimates of chlamydia and gonorrhoea in the Netherlands

Abstract: Chlamydia and gonorrhoea prevalence were low in the general Dutch population, as was the participation rate. Repeated prevalence surveys are needed to analyse trends in STI prevalences and to evaluate control policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
2
19
0
2
Order By: Relevance
“…However, we failed to show any decline in the prevalence of UU, CT, or NG, and the overall UU, CT, and NG prevalence found here was distinctly higher than estimates from high-income countries. 20,21 Comprehensive screening guidelines and treatment policies should be conducted to control the population prevalence.…”
Section: The Co-infection Of Uu Ct and Ngmentioning
confidence: 99%
“…However, we failed to show any decline in the prevalence of UU, CT, or NG, and the overall UU, CT, and NG prevalence found here was distinctly higher than estimates from high-income countries. 20,21 Comprehensive screening guidelines and treatment policies should be conducted to control the population prevalence.…”
Section: The Co-infection Of Uu Ct and Ngmentioning
confidence: 99%
“…As chlamydia rates did not change, one should consider focusing on disease management (i.e. prevention of long-term complications of chlamydia) instead of finding all chlamydia infections by extensive testing 20 . Surveillance of long-term complications is needed, including the identification of those with the highest risk of complications based on, amongst others, genetic markers.…”
Section: Blood Donorsmentioning
confidence: 99%
“…Behavioural interventions are often STI clinic-based 32,34 , as individuals visiting the STI clinic at sexual health centers (SHC) tend to engage in higher risk sexual behaviour than the general population 35,36 , and potentially benefit the most from behavioural interventions 34 . It was previously shown that individuals who were diagnosed with a chlamydia infection engaged in more risk-reducing sexual behaviour after receiving the test results, whereas individuals who tested chlamydia negative did not change their sexual behaviour or even engaged in behaviours related to increased risk (i.e., decreased condom use) after testing 9,10,37 .…”
mentioning
confidence: 99%